Analysis of the Role of Baznas Village Microfinance in Empowering the Economy of Micro-Entrepreneurs Among Mustahik - Ubed, Fahrul; Mugiyati, Mugiyati (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Baznas Village Microfinance (BMD) is one of the programs initiated by the National Zakat Amil Agency (BAZNAS), designed to support mustahik micro-businesses in specific areas. BAZNAS is the official and sole institution established by the government under Presidential Decree No. 8 of 2001, tasked with collecting and distributing zakat, infaq, and alms (ZIS) at the national level. This research aims to analyze the Baznas Village Microfinance program in empowering the economy of mustahik micro-entrepreneurs. The study employs a qualitative approach through field research and literature review. Data collection methods include observation and interviews, which are then analyzed and presented qualitatively. The findings indicate that the Baznas Village Microfinance program significantly contributes to improving access to business capital, enhancing economic conditions, and providing entrepreneurship training for beneficiaries through the utilization of productive zakat funds. As a result, the program effectively empowers the economy of mustahik micro-businesse